A nitrogen-doped titanium dioxide modified asphalt with tail gas degradation function and its preparation method and application
By dispersing the combination of nano N-TIO2 with asphalt, the high-speed shear method is used to solve the visuality and durability of nano TIO2 on the road, and achieve efficient degradation effect. Consumption.
Patent Information
- Application Number
- CN202411482650.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The prior art When using nano-TiO2 as a photocatalytic material, direct coating on the road will interfere with the visibility of the mark, and the durability of the coating needs to be further evaluated under traffic wear. At the same time, the high-temperature preparation process consumes a lot of energy and lacks the correctness. Detailed control of process parameters.
By mixing nano-N-TiO2 powder with 90# matrix asphalt or SBS modified asphalt, dispersing using high-speed shearing method, controlling the stirring temperature and shearing speed, and finally developing at 120°C for 30 minutes to ensure the stability of the nanoparticles. Uniform dispersion and basic properties of bitumen.
The nano N-TIO2 is evenly scattered in the asphalt, reducing the viscosity of asphalt, improving the effect of tail gas degradation, and a simple process, low energy consumption, and good product performance.
Smart Images

Figure CN119019859B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of road maintenance materials, and in particular to a nitrogen-doped titanium dioxide modified asphalt with tail gas degradation function, a preparation method and application thereof. Background Art
[0002] According to statistics, by the end of 2023, the national highway mileage will reach 5.4368 million kilometers, and the number of motor vehicles will reach 435 million. Exhaust emissions have become the main source of air pollution in China. CO, HC, NOx and solid suspended particles in exhaust gas will form haze. How to control automobile exhaust pollution has become a difficult problem for countries around the world. It is a general trend to expand the measures to control exhaust pollution from mandatory administrative measures and improvements to motor vehicle exhaust systems to the ability of pavements to absorb and degrade exhaust gas. The national highway maintenance mileage exceeds 5.3503 million kilometers. The pavement mainly based on asphalt concrete shows early destructive behavior due to severe loads, harsh environments and other factors, which seriously affects the service performance and sustainable development of the highway. It is necessary to directly lay a layer of asphalt concrete surface layer on the original pavement to improve the quality of the pavement and improve the pavement service level. For example, adding a photocatalytic material (N-TiO2) that can decompose exhaust gas during the pavement paving process can well solve the two problems of exhaust pollution and repairing the functional layer. Since N-TiO2 is a nanoscale bright white powder material, direct coating will interfere with the visibility of road signs, and the durability of the coating under traffic wear also needs to be further evaluated. By adding TiO2 to asphalt pavement materials, the wear caused by continuous traffic will gradually expose the nanoparticles wrapped in the asphalt film, giving the pavement a continuous exhaust gas degradation effect. The method of adding N-TiO2 as a modifier to asphalt is more economical.
[0003] Due to the quantum size effect, discontinuity of electronic energy levels, small size effect, quantum tunneling effect and surface interface effect of nanoparticles, nanomaterials are very easy to combine with other atoms to achieve a stable state. Adding them to asphalt will cause great changes in the asphalt system. At present, the commonly used methods for preparing modified asphalt are high-speed shearing method, mechanical stirring method and solvent method. Some studies believe that the mechanical stirring method cannot achieve a good modification effect, and the solvent preparation of the solvent method is complicated and requires anti-segregation measures, so this paper adopts the high-speed shearing method. Since nanoparticles have a large specific surface area and high surface energy, they are easy to agglomerate if added to asphalt with high viscosity. The high-speed shearing method can heat the asphalt during the modification process, reduce the viscosity, and is conducive to the dispersion of nanoparticles. At the same time, it provides high-speed shearing stirring to further promote the dispersion of nanoparticles. However, in order to reduce the viscosity of asphalt, the preparation temperature of modified asphalt must be increased to promote the uniform dispersion of nanoparticles. High temperature will cause asphalt aging and waste energy, so the temperature should not be too high, and the two will conflict. Therefore, the key to the research is to introduce a reasonable dose of nanoparticles to ensure that the nanoparticles are evenly dispersed in the asphalt and to prevent asphalt aging. At the same time, further research on the mechanism and microstructure of TiO2 modified asphalt will have guiding significance for engineering practice.
[0004] Considering different types of asphalt, polymer and nanomaterials, the preparation process of nanomaterial modified asphalt may be very different. Therefore, controlling the process parameters such as shear rate, temperature, time and whether high temperature development process is required to prepare nanomaterial modified asphalt with good compatibility and good thermal storage stability is a future research direction.
[0005] After searching, Zhao Wenhui et al. (Study on viscoelastic properties and phase structure of nano-modified asphalt based on rheology [J]. Bulletin of Silicate, 2020(011):039.) added nanoparticles to the molten matrix asphalt at 1%, 3%, and 5% asphalt mass fraction, sheared and dispersed at a shear speed of 4000r / min for 30min, then adjusted to 7000r / min for high-speed shearing for another 30min, and the temperature of the entire preparation process was controlled at 160℃ to obtain nanomaterial modified asphalt. Fan Liang et al. (Study on road performance and anti-aging effect of nano-TiO2 modified asphalt [J]. New Chemical Materials. 2019(7)) used an electric constant temperature drying oven to heat the matrix asphalt to a molten state, added nano-TiO2 powder at mass fractions of 15%, 25%, 35%, and 55%, respectively, stirred evenly with an electric stirrer, and high-speed sheared and dispersed at a high speed of 5000r / min with a shearing time of 25min to obtain nano-TiO2 modified asphalt. Zhang Chunqing et al. (Study on the Anti-ultraviolet Aging Ability of Nano-TiO2 Modified Asphalt [J]. Highway and Automobile Transport, 2011 (3): 4) heated the base asphalt to 160℃ until it was molten, added nano-TiO2 powder at mass fractions of 1%, 2%, and 3%, respectively, started the high-speed shearing machine, and gradually added rutile nano-TiO2 into the asphalt with a small spoon at about 165℃. After the bubbles in the asphalt were basically discharged, the next spoon was added until it was completely added; the shearing and stirring were continued at 165℃ for about 20 minutes. Before the end of the stirring, the speed was gradually reduced to completely eliminate the bubbles in the asphalt. Finally, the asphalt was placed in an oven for development for 30 minutes to complete the preparation. The above literature provides technical references for the preparation method of nanomaterial modified asphalt, but lacks detailed preparation parameters such as the stirring time of nanoparticles and asphalt, shear speed, and high temperature development temperature.
[0006] Zhong Xi et al. (Study on the influence of different modified materials on the performance of matrix asphalt [J]. Journal of Qinghai University, 2022, 40(6): 68-75.) modified the original asphalt by single doping of 6 materials, with a mass fraction of 4%. The test schemes were original asphalt (A), A+4% nano ZnO (B), A+4% nano SiO2 (C), A+4% nano TiO2 (D), A+4% SEBS (E), A+4% SBR (F), and A+4% EVA (G). The preparation process was to place the matrix asphalt in an oven at 140°C for 90 minutes to make the asphalt molten, add the 6 modifiers, and stir manually for 15 minutes to dissolve the nano powder into the asphalt. A high-speed mixer was used to disperse the asphalt at a shear speed of 5000 r / min at 165°C for 60 minutes, and then continue stirring for 10 minutes to remove bubbles. Then, the asphalt was placed in an oven at 155°C for swelling and development for 60 minutes, and the modification was completed. Li Yuwei (Preparation and Temperature Control Characteristics of TiO2 Quantum Dot Modified Asphalt [D]. Southeast University, 2022. DOI: 10.27014 / d.cnki.gdnau.2022.001818.) Use an oven to heat the base asphalt to a molten state at 160°C; slowly and uniformly add TiO2 quantum dot powder with asphalt mass fractions of 5%, 10% and 20% to the base asphalt, and stir for 30 minutes to disperse the titanium dioxide quantum dots in the asphalt; set the high-speed shearing machine to 4500-5000r / min for shearing and stirring for 1-1.5h. After the shearing is completed, place it in an oven at 130°C for 0.5h to ensure that the titanium dioxide quantum dots are evenly dispersed in the base asphalt, thus obtaining titanium dioxide quantum dot modified asphalt.
[0007] In the above literature, during the preparation process of nanomaterial modified asphalt, the asphalt preheating temperature, stirring temperature and high-temperature development temperature are high, the shearing time is long, and the energy consumption is high. No control experiments are conducted to test the effects of changes in temperature, shearing time, development time, etc. on the basic properties of nanomaterial modified asphalt.
[0008] Therefore, in view of the above situation, there is an urgent need to provide a nitrogen-doped titanium dioxide modified asphalt with exhaust gas degradation function and a preparation method and application thereof to overcome the shortcomings in current practical applications. Summary of the invention
[0009] The purpose of the present invention is to provide a nitrogen-doped titanium dioxide modified asphalt with exhaust gas degradation function and a preparation method and application thereof, so as to solve the problems in the above-mentioned background technology.
[0010] In order to solve the above technical problems, the present invention provides a nitrogen-doped titanium dioxide modified asphalt with exhaust gas degradation function, which comprises the following raw materials in parts by mass:
[0011] 1-5 parts of nano N-TiO2 powder and 99-95 parts of asphalt.
[0012] As a further solution of the present invention: the asphalt is 90# base asphalt or finished SBS modified asphalt with an SBS mass fraction of 5%.
[0013] As a further solution of the present invention: the preparation method of the nitrogen-doped titanium dioxide modified asphalt with exhaust gas degradation function as described above comprises the following steps:
[0014] Step 1: heating the asphalt to a molten state;
[0015] Step 2: Stir the molten asphalt, then add N-TiO2 powder 20 times at 60s intervals using an electronic weighing spoon, and stir for a total of 30 minutes.
[0016] Step 3: Use DXY-12H constant temperature oil bath pot and FLUKO-FM300 high-speed shear dispersing emulsifier to shear and disperse nano N-TiO2;
[0017] Step 4: Place the sheared and dispersed modified asphalt into a HS841-6 electric heated blast drying oven for high temperature development at 120°C for 30 minutes to make the N-TiO2 distribution more uniform. The preparation is completed.
[0018] As a further solution of the present invention: in step 1, the asphalt is heated using a HS841-6 electric heating blast drying oven, wherein if 90# base asphalt is selected, it is heated to 135°C, and if SBS modified asphalt is selected, it is heated to 163°C.
[0019] As a further solution of the present invention: in step 2, a DXY-12H constant temperature oil bath is used in combination with an electric stirrer to stir the molten asphalt for 5-10 minutes.
[0020] As a further solution of the present invention: in step 2, if 90# base asphalt is selected, the stirring temperature is controlled to be 135°C; if SBS modified asphalt is selected, the stirring temperature is controlled to be 163°C.
[0021] As a further solution of the present invention: in step 3, the shearing speed is 5000 r / min and the shearing time is 50 min.
[0022] As a further solution of the present invention: in step 3, if 90# base asphalt is selected, the shear dispersion temperature of 90# base asphalt is controlled at 160°C; if SBS modified asphalt is selected, the shear dispersion temperature is controlled at 170°C.
[0023] As a further solution of the present invention: the nitrogen-doped titanium dioxide modified asphalt with exhaust gas degradation function is used in the degradation of automobile exhaust gas.
[0024] As a further solution of the present invention: the automobile exhaust gas is selected from nitrogen oxides in toxic and harmful automobile exhaust gases.
[0025] By adopting the above technical solution, the present invention has the following beneficial effects:
[0026] The present invention does not use any additives other than N-TiO2, but adjusts the basic properties of N-TiO2 modified asphalt by changing the preparation process. The prepared product can degrade automobile exhaust and has broad market value and application prospects.
[0027] The present invention reduces the mixing temperature of 90# matrix asphalt and nano N-TiO2 to 135°C, at which the nano particles can be well dissolved in the 90# matrix asphalt. 160°C is a more suitable shear dispersion temperature, at which the nano N-TiO2 particles are evenly dispersed in the asphalt, which is equivalent to forming countless tiny aggregate particles, tightly combining the asphalt materials together;
[0028] The present invention fixed the shear rate at 5000±500r / min and the shear time at 50±5min. The N-TiO2 modified asphalt prepared under this condition has better performance, indicating that this condition is most conducive to the dispersion of nanoparticles in asphalt. Shearing makes the modified asphalt system more uniform. Too high a shear rate may cause the hydrocarbon molecules in the asphalt to break, reduce the ductility, and increase the temperature inside the asphalt. If the shear speed is low, the nanoparticles are unevenly dispersed.
[0029] The present invention reduces the high temperature development temperature to 120°C and analyzes the development time. By controlling the development time, the basic properties of N-TiO2 modified asphalt are adjusted to ensure product quality. The asphalt with a development time of 30 minutes has better performance.
[0030] The N-TiO2 modified asphalt prepared by the present invention is frozen before the exhaust gas degradation test, and then the asphalt film is polished with sandpaper to achieve a wear mass loss of 0.5%, simulating the road surface worn by vehicle tires, so that more nano N-TiO2 particles are exposed to the air, which is more in line with the actual situation of the asphalt road surface in operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1The flowchart of the preparation of nitrogen-doped titanium dioxide modified asphalt with tail gas degradation function in the present invention;
[0033] Figure 2 This is an AFM two-dimensional morphology image of the nitrogen-doped titanium dioxide modified asphalt with exhaust gas degradation function in the present invention;
[0034] Figure 3 are the complex modulus and phase angle of the nitrogen-doped titanium dioxide modified asphalt with tail gas degradation function in the present invention;
[0035] Figure 4 is the rutting factor of the nitrogen-doped titanium dioxide modified asphalt with exhaust gas degradation function in the present invention;
[0036] Figure 5 It is the automobile exhaust degradation efficiency of the nitrogen-doped titanium dioxide modified asphalt with exhaust degradation function in the present invention. DETAILED DESCRIPTION
[0037] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.
[0039] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention will be understood according to specific circumstances.
[0040] The present invention is further explained below in conjunction with specific implementation modes.
[0041] See also Figure 1-Figure 5The embodiment of the present invention provides a nitrogen-doped titanium dioxide (N-TiO2) modified asphalt with exhaust gas degradation function, which includes the following raw materials in parts by mass:
[0042] 1-5 parts of nano N-TiO2 powder and 99-95 parts of asphalt; the asphalt is 90# base asphalt or finished SBS modified asphalt with SBS mass fraction of 5%.
[0043] See also Figure 1-Figure 5 The method for preparing the nitrogen-doped titanium dioxide modified asphalt with exhaust gas degradation function provided in an embodiment of the present invention comprises the following steps:
[0044] Step 1: heating the asphalt to a molten state;
[0045] Step 2: Stir the molten asphalt, then add N-TiO2 powder 20 times at 60s intervals using an electronic weighing spoon, and stir for a total of 30 minutes.
[0046] Step 3: Use DXY-12H constant temperature oil bath pot and FLUKO-FM300 high-speed shear dispersing emulsifier to shear and disperse nano N-TiO2;
[0047] Step 4: Place the sheared and dispersed modified asphalt into a HS841-6 electric heating blast drying oven for high temperature development at 120°C for 30 minutes to make the N-TiO2 distribution more uniform, and the preparation is completed;
[0048] In step 1, the asphalt is heated in a HS841-6 electric heating blast drying oven, wherein if 90# base asphalt is selected, it is heated to 135°C, and if SBS modified asphalt is selected, it is heated to 163°C;
[0049] In step 2, use a DXY-12H constant temperature oil bath pot and an electric stirrer to stir the molten asphalt for 5-10 minutes;
[0050] In step 2, if 90# base asphalt is selected, the stirring temperature is controlled to be 135°C; if SBS modified asphalt is selected, the stirring temperature is controlled to be 163°C;
[0051] In step 3, the shearing speed is 5000 r / min and the shearing time is 50 min;
[0052] In step 3, if 90# matrix asphalt is selected, the shear dispersion temperature is controlled at 160°C; if SBS modified asphalt is selected, the shear dispersion temperature is controlled at 170°C;
[0053] If N-TiO2\SBS composite modified asphalt is prepared, the preheating and stirring temperature of SBS modified asphalt is controlled at 163°C, the shear dispersion temperature is 170°C, and other preparation processes remain unchanged.
[0054] The present invention provides the use of the above-mentioned N-TiO2 modified asphalt in the degradation of automobile exhaust, wherein the automobile exhaust is nitrogen oxides and the ultraviolet light intensity is 10mW / cm 2 , 20mW / cm 2 、30mW / cm 2 , relative humidity is 50%, and NO gas flow rate is 4L / mim, which is within the exhaust emission range of ordinary cars.
[0055] The invention has reasonable design, simple process and easily controlled reaction conditions. No additives other than N-TiO2 are used in the preparation process. Conventional instruments and equipment, 90# matrix asphalt or SBS modified asphalt can be purchased in building material stores. The obtained N-TiO2 modified asphalt can degrade automobile exhaust and exert the proper function of the material.
[0056] See also Figure 1-Figure 5 The embodiment of the present invention provides an application of the nitrogen-doped titanium dioxide modified asphalt with exhaust gas degradation function in the degradation of automobile exhaust gas; the automobile exhaust gas is selected from nitrogen oxides in toxic and harmful automobile exhaust gas.
[0057] Example 1: The mass ratio is 1 part of nano N-TiO2 powder and 99 parts of 90# matrix asphalt. Use DXY-12H electric stirring constant temperature oil bath to stir the molten asphalt for 5-10 minutes, then add N-TiO2 powder 20 times with an electronic weighing spoon at an interval of 60 seconds while stirring, and control the stirring temperature to 135°C for a total of 30 minutes. Adjust the height of the bracket so that the bottom of the high-speed shear dispersing emulsifier head is about 1 cm away from the bottom of the constant temperature oil bath container. Set the temperature of the DXY-12H constant temperature oil bath to quickly raise the asphalt to 160°C, shear and disperse the easily agglomerated N-TiO2 powder, the shear speed is 5000r / min, and the shear time is 50min. The sheared and dispersed N-TiO2 modified asphalt is placed in the HS841-6 electric heating blast drying oven for high temperature development at 120°C for 0, 30min and 60min for comparative tests, and the preparation is completed.
[0058] Example 2: In this example, a nitrogen-doped titanium dioxide (N-TiO2) modified asphalt with exhaust gas degradation function is prepared, and the preparation method thereof is as shown in the above-mentioned Example 1; different from Example 1, in this example, the mass ratio is 3 parts of nano N-TiO2 powder and 97 parts of 90# base asphalt.
[0059] Example 3: In this example, a nitrogen-doped titanium dioxide (N-TiO2) modified asphalt with exhaust gas degradation function is prepared, and the preparation method thereof is as shown in the above-mentioned Example 1; different from Example 1, in this example, the mass proportion is 5 parts of nano N-TiO2 powder and 95 parts of 90# matrix asphalt.
[0060] Comparative Example 1: In this example, a nitrogen-doped titanium dioxide (N-TiO2) modified asphalt with exhaust gas degradation function is prepared. The preparation method thereof is as shown in the above-mentioned Example 1. Different from Example 1, in this comparative example, the shear speed is 4000 r / min.
[0061] Comparative Example 2: In this example, a nitrogen-doped titanium dioxide (N-TiO2) modified asphalt with exhaust gas degradation function is prepared, and the preparation method thereof is as shown in the above-mentioned Example 1; Different from Example 1, in this comparative example, the stirring temperature is controlled at 160°C, and the shear dispersion time is 30min, 60min and 90min respectively, and the asphalt after shear dispersion is stirred for 60min using a DXY-12H constant temperature oil bath pot and an electric stirrer, and the stirring temperature is 160°C.
[0062] Comparative Example 3: In this embodiment, a nitrogen-doped titanium dioxide (N-TiO2) modified asphalt with exhaust gas degradation function is prepared, and the preparation method thereof is as shown in the above-mentioned Comparative Example 3; different from Comparative Example 2, the shear dispersion time is changed to 10min, 20min and 30min, and the mass ratio is 3 parts of nano N-TiO2 powder and 97 parts of 90# matrix asphalt.
[0063] Comparative Example 4: In this embodiment, a nitrogen-doped titanium dioxide (N-TiO2) modified asphalt with exhaust gas degradation function is prepared, and the preparation method thereof is as shown in the above-mentioned Comparative Example 2; different from Comparative Example 2, in this Comparative Example, the stirring time is 10 minutes, the shear speed is 5000r / min, 6000r / min and 7000r / min, the high-temperature standing development temperature is 160°C, the time is 10 minutes, and the mass ratio is 5 parts of nano N-TiO2 powder.
[0064] N-TiO2 modified asphalt performance test
[0065] The test results are as follows:
[0066] 1. Softening point, penetration and elongation
[0067] Table 1 Preparation of N-TiO2 modified asphalt
[0068] (1) Needle penetration
[0069] The penetration of asphalt reflects the viscosity and hardness of asphalt at the test temperature, and is a manifestation of the cohesion of the asphalt system. As shown in Example 1, Example 2, and Example 3 in Table 1, the penetration of N-TiO2 modified asphalt decreases with the increase of N-TiO2 dosage and decreases with the growth time, indicating that the stiffness of N-TiO2 modified asphalt increases with the increase of dosage and growth time. The addition of nano-N-TiO2 greatly improves the viscosity of asphalt, and the larger activation energy of the nano-N-TiO2 surface makes it more tightly combined with asphalt.
[0070] (2) Softening point
[0071] The softening point of asphalt can reflect the ability of asphalt to maintain its original viscosity and plasticity when heated, that is, heat resistance. As shown in Example 1, Example 2, and Example 3 in Table 1, the softening point of N-TiO2 modified asphalt increases with the increase of N-TiO2 dosage and increases with the growth time. Because the specific surface area of nano N-TiO2 is large, it will adsorb the light components in the asphalt system, so that the content of asphaltene increases relatively. The stirring and shearing process also has a certain destructive effect on the composition and structure of asphalt. The combined effect of the two causes the light components in the asphalt to volatilize, and the corresponding heavy component content will increase to a certain extent, resulting in a decrease in the temperature sensitivity of the asphalt, thereby increasing the softening point of the modified asphalt.
[0072] (3) Elongation
[0073] Ductility characterizes the ability of asphalt materials to produce plastic deformation under tensile force under certain temperature conditions. As shown in Example 1, Example 2, and Example 3 in Table 1, the ductility of N-TiO2 modified asphalt decreases with the increase of N-TiO2 dosage. The ductility value at high temperature development of 30min is significantly higher than that at 0min and 60min, which indicates that nano N-TiO2 has an adverse effect on the low-temperature ductility of asphalt. This phenomenon may occur because the addition of N-TiO2 to the base asphalt produces particle load, which promotes the increase of viscosity and stiffness of the asphalt material; and N-TiO2 absorbs light components in the asphalt, which indirectly increases the asphaltene content. As the amount of N-TiO2 increases, the formed particle agglomeration becomes more difficult to open, and the particle agglomeration phenomenon is visually manifested as a decrease in ductility.
[0074] From Comparative Examples 2, 3, and 4 in Table 1, it can be seen that when the mixing and stirring temperature and the development temperature of the 90# matrix asphalt and the nanoparticles are increased to 160°C, or the shear speed is increased, or the shear time is extended, the increased temperature, excessive stirring, or excessive shear dispersion will destroy the asphalt system. From the fracture of the ductility test piece, it can be observed that the toughness of the asphalt decreases rapidly, and the asphalt is easily broken, resulting in a significant decrease in the penetration and ductility, and an increase in the softening point. However, when the shear speed is low and the shear time is short, the nanoparticles are not evenly dispersed in the asphalt, and small particles that are not dispersed can be seen from the fracture of the ductility test piece.
[0075] From the test results of the three major indicators of N-TiO2 modified asphalt, it can be seen that the asphalts of Example 1, Example 2, and Example 3 developed at high temperature for 30 minutes have better performance, and it is worthwhile to conduct more tests on them. The reason may be that the van der Waals force and electrostatic force between the nanoparticles will cause agglomeration. The agglomeration force is relatively weak and can be reduced with the help of certain external forces. Considering the characteristics of easy agglomeration of nanomaterials and referring to the swelling mechanism of polymer-modified asphalt, this patent analyzes the high-temperature standing time of N-TiO2 modified asphalt, which is mainly divided into two situations: one is to place the shear-dispersed N-TiO2 modified asphalt in a HS841-6 electric hot air drying oven at 120°C for 30 minutes and 60 minutes; the other is to continue to stir the dispersed N-TiO2 modified asphalt for 60 minutes; the above two situations are compared with the situation of pouring immediately after shear dispersion. The basic performance is shown in Table 1. The results of various indicators show that the basic performance index of the sample developed at 120℃ for 30 minutes after shear dispersion is the best, indicating that the high temperature development for 30 minutes is enough to meet the time required for the nano-N-TiO2 to continue to interact with the 90# matrix asphalt, making the N-TiO2 more evenly dispersed. The microscopic morphology is shown in Figure 2 .
[0076] 2. Complex shear modulus and phase angle
[0077] The complex shear modulus is the ratio of the maximum shear stress to the strain, which indicates the total deformation resistance of asphalt, while the phase angle is the embodiment of the hysteresis of material stress and strain. The larger the phase angle, the greater the proportion of viscous components in the asphalt, and the smaller the phase angle, the greater the proportion of elastic components. Figure 3 It can be seen that with the increase of N-TiO2 dosage, the complex modulus of N-TiO2 modified asphalt decreases and the phase angle increases, indicating that after high-temperature heating, N-TiO2 modified asphalt is converted from part of the elastic component to the viscous component, and the deformation recovery ability and deformation resistance are weakened. N-TiO2 enhances the high-temperature performance of asphalt.
[0078] 3. Rutting factor
[0079] The rutting factor is the ratio of the complex modulus to the sine of the phase angle (G * / sinδ), can be used to evaluate the anti-rutting performance of asphalt. A higher rutting factor means that the modified asphalt has better resistance to high temperature deformation. Figure 4 It can be seen that the rutting factor of N-TiO2 modified asphalt is greater than that of base asphalt, indicating that the addition of nano-N-TiO2 improves the elastic properties of base asphalt and its ability to resist deformation under high temperature and long-term load is better.
[0080] 4. Automobile exhaust degradation
[0081] Taking nitrogen oxides as an example, a set of real-time degradation reaction device was made to test and analyze the efficiency of N-TiO2 modified asphalt in real-time degradation of NO. The whole device consists of an exhaust generator, an ultraviolet lamp, a gas reaction chamber, a nitrogen oxide analyzer and a gas flow meter. The size of the asphalt film is 90mm×90mm×1mm, and the mass of the asphalt is 6g. Before the test, the asphalt film was frozen and then polished with sandpaper. The wear mass loss rate was 0.5%, simulating the wear of vehicle tires on the road surface. The test process is as follows:
[0082] (1) Open the top cover of the reaction chamber, place the specimen in the reaction chamber, adjust the height so that the gas just passes through the surface of the specimen, and then close the reaction chamber cover. The reaction chamber cover is made of transparent glass with stainless steel edges to allow ultraviolet light to reach the surface of the test sample. There are air inlets and outlets on both sides of the reaction chamber to keep the gas flowing continuously in the reaction chamber. The NOx analyzer records the concentration data of NO, NO2 and NOx in the reaction chamber in real time, and the data recording interval is 6s.
[0083] (2) Open the air supply valve to control the NO gas flow rate to 4L / min, which is within the exhaust emission range of ordinary cars. The gas concentration is stable at 1000±50ppb. Use 25℃ water vapor to control the relative humidity to 50%. The UV intensity irradiated on the surface of the specimen is 10mW / cm 2 , 20mW / cm 2 、30mW / cm 2 .
[0084] (3) When the gas concentration becomes constant, turn on the UV lamp to activate the photocatalytic process. This is recorded as the initial value of the NO concentration. C 0 As the photocatalysis proceeded, the NO concentration was recorded as C i , NO degradation rate is η=(C 0 -C i ) / C 0 *100% , ηThe larger the value, the better the exhaust gas degradation efficiency. During the test, the concentration of NO2 was kept at a low level, so the photocatalytic ability of the sample was characterized by the NO degradation rate. Taking N-TiO2 modified asphalt grown at 120℃ for 30min as an example, its NO degradation efficiency was tested. The exhaust gas degradation efficiency of N-TiO2 modified asphalt with different dosages is shown in Figure 5 .Depend on Figure 5 It can be seen that the exhaust gas degradation efficiency increases with the increase of N-TiO2 dosage and the increase of light intensity, which means that the more nano-N-TiO2 there is on the asphalt surface and the greater the light intensity, the higher the catalytic efficiency. 2 The catalytic efficiency is slightly lower than 20mW / cm 2 The reason may be that there are few N-TiO2 nanoparticles in the asphalt, and increasing the light intensity does not substantially increase the catalytic efficiency.
[0085] The technical advantage of the present invention is that the basic performance of the prepared N-TiO2 modified asphalt meets the requirements without adding any additives, and at the same time has the efficiency of degrading automobile exhaust.
[0086] The test selected the finished nano N-TiO2 produced by Xuancheng Jingrui New Materials Co., Ltd. The basic technical indicators are shown in Table 2:
[0087] Table 2 Basic technical indicators of N-TiO2
[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A nitrogen-doped titanium dioxide modified asphalt with tail gas degradation function, characterized in that: According to the weight percentage, it includes the following raw materials: 1-5 parts of nano N-TiO2 powder and 99-95 parts of asphalt; The asphalt is 90# base asphalt; The preparation method of nitrogen-doped titanium dioxide modified asphalt with tail gas degradation function comprises the following steps: Step 1: heating the asphalt to a molten state; Step 2: Stir the molten asphalt, then add N-TiO2 powder 20 times at 60s intervals using an electronic weighing spoon, and stir for a total of 30 minutes. Step 3: Use DXY-12H constant temperature oil bath pot and FLUKO-FM300 high-speed shear dispersing emulsifier to shear and disperse nano N-TiO2; Step 4: Place the sheared and dispersed modified asphalt into a HS841-6 electric heating blast drying oven for 30 minutes at 120°C to make the N-TiO2 distribution more uniform. The preparation is completed; In step 2, the stirring temperature is controlled to be 135°C; In step 3, the shearing speed is 5000 r / min and the shearing time is 50 min; In step 3, the shear dispersion temperature is controlled to be 160°C.
2. The nitrogen-doped titanium dioxide modified asphalt with exhaust gas degradation function according to claim 1, characterized in that: In step 1, the asphalt is heated to 135° C. using a HS841-6 electric heating blast drying oven.
3. The nitrogen-doped titanium dioxide modified asphalt with exhaust gas degradation function according to claim 2, characterized in that: In step 2, use a DXY-12H constant temperature oil bath pot and an electric stirrer to stir the molten asphalt for 5-10 minutes.
4. Use of the nitrogen-doped titanium dioxide modified asphalt with exhaust gas degradation function according to claim 1 in automobile exhaust gas degradation.
5. The use according to claim 4, characterized in that: The automobile exhaust gas is selected from nitrogen oxides in toxic and harmful automobile exhaust gases.
Citation Information
Patent Citations
Nano modified asphalt and preparation method thereof
CN110499036A
High-mixing-amount rubber powder-SBS composite modified asphalt and preparation method thereof
CN113429802A